Digital inclusive finance penetration and household debt maturity structure: Empirical estimation based on China Family Panel Studies Data - Jiayu Hou; Yingli Zhang (PLoS ONE, 2025)
This paper analyzes how the penetration of digital inclusive finance affects the maturity structure of household debt by matching data from the Peking University Digital Inclusive Finance Index and China Family Panel Studies (CFPS). Based on the conclusion, the broader penetration of digital inclusive finance has significantly improved the households’ long-term debt level, thereby contributing to a longer-term trend in the maturity structure of household debt. Simultaneously, the effect is more evident in households with high income, large consumption expenditure, low asset levels, and no credit constraints, as well as households in central and western regions and those with high housing prices. According to the mechanism research, there are three transmission channels: the liquidity constraint of credit, household mental accounting, and the traditional bank competition. Therefore, we should focus not only on how digital inclusive finance impact on the overall scale of household debt, but also on how to create a reasonable debt maturity structure conducive to prevent financial risks.